A query language for multi‐version data web archives. Issue 4 (8th July 2016) - Meimaris, Marios; Papastefanatos, George; Viglas, Stratis; Stavrakas, Yannis; Pateritsas, Christos; Anagnostopoulos, Ioannis
Abstract: The Data Web refers to the vast and rapidly increasing quantity of scientific, corporate, government and crowd‐sourced data published in the form of Linked Open Data, which encourages the uniform representation of heterogeneous data items on the web and the creation of links between them. The growing availability of open linked datasets has brought forth significant new challenges regarding their proper preservation and the management of evolving information within them. In this paper, we focus on the evolution and preservation challenges related to publishing and preserving evolving linked data across time. We discuss the main problems regarding their proper modelling and querying and provide a conceptual model and a query language for modelling and retrieving evolving data along with changes affecting them. We present in details the syntax of the query language and demonstrate its functionality over a real‐world use case of evolving linked dataset from the biological domain.